"Husband under the Bed": Specular Enclosures, Cuckoldry, and Logorrhea in Dostoevsky's Early Works. Issue 2 (10th March 2017) - ERMAN, IRINA
Abstract : This article seeks to demonstrate how Dostoevsky processes the devices vaudeville, folk theater, and particularly the cuckold play into his own unique, genre‐bending art form. By focusing on his overlooked 1848 half‐vaudeville, half‐feuilleton "The Other Man's Wife and the Husband under the Bed, " and placing it in the context of his other works, I explore the influence of the cuckold play on Dostoevsky's tendency to privilege two‐in‐one scenarios, such as doubling, and sometimes the literal enclosure of two men in one tight space. I argue that the main concern that emerges from Dostoevsky's theatrical influences is the relationship between discourse and space. Specifically, in contrast to Bakhtin's focus on "thresholds" as the paradigmatic loci of Dostoevsky's poetics, I point out the way that spatial and specular enclosures originate excessive, logorrheic discourse and the dialogization, or doubling of the characters' inner monologues.